IMPLEMENTASI PERATURAN DAERAH NOMOR 2 TAHUN 2017 TERHADAP PENGARUSUTAMAAN GENDER DALAM PEMERINTAHAN DAERAH DI KABUPATEN SOPPENG - Firman, Heri Afriady; Rahmiati, Rahmiati (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2020)
This study aims to describe the implementation of Regional Regulation No. 2 of 2017 Against Gender Mainstreaming in Regional Government in Soppeng Regency as well as supporting and inhibiting factors in the implementation of gender mainstreaming in Soppeng Regency. This research includes the type of descriptive qualitative field research (field research). The results of this study indicate that the Regional Regulation on Gender Mainstreaming has been implemented in increasing women's participation in the public sphere related to women has been compared with men with the number of women in the government sector which then has implications for government policies and budgets that are gender-responsive, however, some women chose strategic positions but could have been made as an indicator of success compared to the years before the present regulation. The implementation of Gender Mainstreaming in Soppeng Regency is supported by a legal umbrella from the government in the form of Regional Regulations or Regents as legalization and affirmation of policies that are responsive to gender that must be applied, will continue to be postponed by the community concerned until it is held firmly by the community as a norm of life or law the living one. Keywords: Implementation; Local regulation; Gender Mainstreaming